"The Vanished Power of the Usual Reign": Jackson Lears, No Place of Grace, and the Struggle for Hegemony in History. Issue 2 (7th July 2021) - Seal, Andrew
Abstract: This reappraisal essay on Jackson Lears's No Place of Grace: Antimodernism and the Transformation of American Culture, 1880–1920 (1981) considers the book's substantial but diffuse influence among historians by examining it against the background of, and in conversation with, the new social history. The success of this subfield in the 1970s and—while morphing into cultural history—the 1980s created professional as well as theoretical problems for practitioners of "old fashioned" history, especially for intellectual historians. Especially confounding was the question of how to theorize the transmission of ideas from intellectual or cultural elites to the rest of society. "History from the bottom up" had posited far more cultural and intellectual autonomy for the subaltern classes than intellectual historians could grant without fundamental changes in method as well as choices of what to write about. No Place of Grace cut through this problem with an array of new theoretical and rhetorical moves, elevating the concept of cultural hegemony to an essential role in the further analysis of elite transmission of ideas. This essay ends by considering the effects of this conceptual breakthrough, including the costs of focusing on subtler forms of domination over the raw effects of physical force and material inequality.